The feasibility of a diet which enhances inositol availability - Moroni, Ramona Frida; Cazzaniga, Emanuela; Palestini, Paola; Sculati, Michele (Progress in Nutrition, 2021)
Background: Supplementation of myo-inositol has proved effective in different pathological conditions associated with insulin-resistance, including polycystic ovary syndrome, diabetes, gestational diabetes, and metabolic syndrome. At the same time, dietary habits in developed countries tend to reduce inositol intake, due to reduced consumption of whole grain foods, legumes, and nuts, rich in phytic acid, the main source of inositol. Aim: The review aims at providing a collection of foods with high phytic acid content to be used for diets that can make available as much inositol as is obtained from nutritional supplements commonly present in the market. Methods: An extensive review concerning the phytic acid content of foods was obtained from literature; furthermore, we designed an exemplifying phytic acid rich diet in by means of a specific nutritional software. Results: Foods with high phytic acid content are: cereals (0.04-3.3% on the dry matter), legumes (0.2-2.4%), oil seeds (0.4-5.7%), and nuts (0.2-9.4%). A moderate amount of phytic acid has been found in root vegetables, tubers and fruits, while low levels are found in the leafy green vegetables. Using these data, we developed an example of weekly diet which provides a mean phytic acid content of 5 g/1660Kcal. Conclusions: This study shows that it is possible to increase phytic acid intake, and consequently inositol availability, by means of an appropriate diet as a complementary treatment to dietary supplements. In people who regularly consume fruits and vegetables, the gut microbiota efficiently degrades phytic acid to myo-inositol phosphate products, therefore this diet could be proposed to patients with increased inositol needs, such as those suffering from polycystic ovary syndrome and in insulin resistance.